Interdisciplinarity as a Means of Doing Theology: Jose Mario Francisco, Jr., SJ, PhD and His Writings - Mendoza, Ruben C (Archīum Ateneo, 2020)
As a Jesuit, Jose Mario Francisco has occupied various positions in the academe as a teacher and an administrator. At the same time, he has engaged in research on various topics such as Asian theology, religious identity, Christology, literary theory, Philippine literature in English, translation, and hermeneutics. A thread that runs through his writings is his interdisciplinary approach to the subject of his inquiry. A particular interest of Francisco in his efforts to understand Filipino Catholicism is his emphasis on mission as translation which for him necessarily involves interpretation.